Purple Urine Bag Syndrome: An Alarming Hue? A Brief Review of the Literature. (1st October 2011) - Khan, Fahad; Chaudhry, Muhammad A.; Qureshi, Noorulain; Cowley, Benjamin
Abstract : Purple urine bag syndrome (PUBS) is a unique disease entity characterized by an alarming purple discoloration of the urine secondary to recurrent urinary tract infections with indigo- and indirubin-producing bacteria. It is usually associated with prolonged urinary catheterization and chronic debilitated states. We hereby present a concise review of this rare phenomenon with historic perspectives, epidemiology, emphasizing on current concepts of etiology, pathogenesis, relevant clinical associations, treatment modalities, prognosis, and future directions in PUBS. In addition, we highlight an interesting occurrence of this intriguing phenomenon in a 39-year-old gentleman at our institution.